Đánh giá hàm lượng PCBs, PAHs, sterol trong nước sông tại Hà Nội và Thành phố Hồ Chí Minh bằng phần mềm AIQS-DB tích hợp trên GCMS - Thảo, Nguyễn Thanh; Hạnh, Dương Thị; Trung, Nguyễn Quang (Vietnam Journal of Chemistry, 2016)
Twenty river water samples were taken seasonally in Hanoi and Ho Chi Minh City and analysed for sterol, PCBs and PAHs by using automated identification and quantification system using GCMS-database (AIQS-DB). The highest concentrations were observed for sterol (0.15 to 65.5 μg/L), followed by PCBs (0.1-17.6 ng/L), and PAHs (0.02-229 μg/L). The detection frequencies of PCBs and PAHs were higher in the dry season compared to the rainy season, which probably due to low water levels of the rivers in the dry season. These compounds were detected at relatively low concentrations; however the presence of these contaminants in river systems may give the bad effect to the aquatic organisms